KAP towards COVID-19: A Case Study of Undergraduate Students in Malaysia - Shahrina Ismail; Sharifah Fairuz Syed Mohamad; Fatin Ahza Rosli; Noor ‘Adilah Ibrahim; Sharifah Najwa Syed Mohamad (USIM Press, 2024)
Vol. 33 No. S4 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences